Outcomes of the Newcastle symposium for the prediction of embankment behaviour on soft soil. (January 2018) - Kelly, R.B.; Sloan, S.W.; Pineda, J.A.; Kouretzis, G.; Huang, J.
Abstract: This paper summarises the outcomes of the symposium held in Newcastle, Australia in September 2016 on predicting the geotechnical behaviour of embankments constructed on soft soils. The paper has three parts. Part A describes the construction and monitoring of an embankment constructed on soft soil improved with prefabricated vertical drains (PVDs), along with a brief summary of the site characterisation study. Part B presents the monitoring data, while Part C focuses on the lessons learnt from the symposium by discussing in detail the predictions and back analyses of settlement, lateral deformation and rate of pore water pressure dissipation.